2022
DOI: 10.1007/s12519-022-00631-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of updated birth weight, length and head circumference charts by gestational age in China with the INTERGROWTH-21st NCSS charts: a population-based study

Abstract: Background INTERGROWTH-21st Newborn Cross-Sectional Study (NCSS) charts were established and recommended for global application. However, whether one international reference is appropriate for all populations is still unclear. We aim to compare the updated Chinese birth size charts by gestational age with INTERGROWTH-21st NCSS charts. Methods A cross-sectional survey was carried out, and the birth weight, length and head circumference of 24,375 infants bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Noteworthy, our previous study comparing the Lithuanian neonatal head circumference reference with the IG-21 showed similar concerning results for term newborns (31). Likewise, other studies from different continents also found their regional neonatal reference charts to be significantly different from the neonatal standards provided by the IG-21 (24,29,(32)(33)(34)(35). In spite of the fact that the IG-21 found some support (36, 37), an increasing number of studies consider the IG-21 with caution including the findings of our study that support this position.…”
Section: Discussionmentioning
confidence: 92%
“…Noteworthy, our previous study comparing the Lithuanian neonatal head circumference reference with the IG-21 showed similar concerning results for term newborns (31). Likewise, other studies from different continents also found their regional neonatal reference charts to be significantly different from the neonatal standards provided by the IG-21 (24,29,(32)(33)(34)(35). In spite of the fact that the IG-21 found some support (36, 37), an increasing number of studies consider the IG-21 with caution including the findings of our study that support this position.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, a retrospective cohort study discovered that the postnatal growth of preterm infants in Shandong province (northern China) was considerably higher than that of the IG-21 growth standards at 40–64 weeks ( 13 ). Zhang et al ( 14 ) also investigated 24,375 infants from 13 cities in China and noticed an inconsistency between the updated Chinese birth size charts and the IG-21 references. However, the domestic data by now are still insufficient to determine whether the IG-21 curves can replace Fenton as an evaluation instrument for premature infants in China.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in urban districts in Beijing, the percentage of LBW fluctuated around 4.0% [ 22 ], and the estimated rate of LBW and PTB in the Guangdong province was 4.14% and 4.16%, respectively [ 23 ]. The prevalence of SGA was 10.1% in 13 developed cities in China [ 24 ]. Our findings also indicate a significantly rising trend of LBW and PTB, and a declining trend of SGA, which is consistent with previous studies [ 8 , 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, advanced maternal age was associated with lower rates of SGA in this study, while prior studies have reported conflicting results [ 18 , 46 ]. The debatable association could be attributed to several reasons: (1) Classifying SGA by various fetal growth curves or birth weight percentiles would lead to differences in the prevalence of SGA [ 24 ]. The birth weight percentiles based on healthy populations, could be more effective for recognizing neonates with intrauterine growth restriction or infant mortality [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%